PENERAPAN EVENT (DIENG CULTURE FESTIVAL) TERHADAP MINAT KUNJUNG WISATAWAN KE DING BANJARNEGARA - Setijadi . .; Yubiharto . . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
This study entitled "The Influence of the Event (Dieng Culture Festival) on the Interest of Visiting Tourists to Dieng Banjarnegara". The purpose of this study was to determine whether the event (Dieng Culture Festival) has an effect on the Interest of Visiting Tourists either individually or both variables together. This research is a quantitative research with a survey method. The population in this study is the tourist end of the DCF Banjarnegara event. The sampling technique used simple random sampling with a sample size of 100 people. The data collection technique used a questionnaire, the tools used as data analysis and hypothesis testing were validity test, reliability test, classical assumption test, multiple linear regression, F test and T test. The results of this study indicate that service quality and trust have an effect on customer loyalty. The contribution value of the variables proposed in this study is only able to explain the purchasing decision variable by 50%. The partial test results of the Variance Value DCF have a positive significant effect on the interest of tourists who visit again. Such tourists rated positive and felt pleasantly about their visit to Banjarnegara District. As it is, tourists have the tendency to make a return visit and manage the DCF (Dieng Culture Festival) as part of their holiday prescription. In increasing the competitiveness of the DCF Banjarnegara event, namely with the growth of the creative economy sector that has the potential to be developed, namely crafts, culinary, performing arts, architecture, music and photography, collective agreement between communities, business players, government and academics on management procedures or regulations and development concepts area is very necessary ,. Increasing public awareness of the importance of cultural preservation, increasing knowledge of good and integrated potential destination management, increasing supervision in the creative economy production process so as to create quality products, able to compete, creating an environment in a comfortable, safe and harmonious destination for DCF visitors.